2002
DOI: 10.1080/00036840110115659
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate cointegration and causality tests of Wagner's hypothesis: evidence from the UK

Abstract: The purpose of this paper is to examine the issue of omitted variables in testing the long run validity of Wagner's hypothesis. Using UK data for the period 1948 to 1997, this paper first investigates the secular relationship between public spending and economic development in a bivariate system. In all cases considered, our bivariate cointegration tests indicate the absence of a long run equilibrium condition. However, the introduction of a third variable (money supply) re-establishes a cointegrating relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 15 publications
2
18
1
4
Order By: Relevance
“…Esto es , la ley de Wagner, establece, que un incremento en el gasto público o un aumento en su participación en el gasto total, debe traducirse en un incremento en el ingreso per cápita en la misma proporción. Ello significaría que la elasticidad entre el ingreso per cápita y el gasto público debería ser igual a uno (Courakis et al , 1993, Chow et al , 2002 Nota: (*) rechazo de la hipótesis nula a un nivel de significa de 5% ; ~ m ax = prueba de la raíz característica máxima (Johansen, 1995, tabla 15.1, p.214). Trace = prueba de la Traza (Mackinnon et al, 1999, t abla II, p.571); r = número de vectores de cointegración rezagos = 3.…”
Section: La Evidencia Empírica La Base De Datos Ut Ilizada Consiste Eunclassified
“…Esto es , la ley de Wagner, establece, que un incremento en el gasto público o un aumento en su participación en el gasto total, debe traducirse en un incremento en el ingreso per cápita en la misma proporción. Ello significaría que la elasticidad entre el ingreso per cápita y el gasto público debería ser igual a uno (Courakis et al , 1993, Chow et al , 2002 Nota: (*) rechazo de la hipótesis nula a un nivel de significa de 5% ; ~ m ax = prueba de la raíz característica máxima (Johansen, 1995, tabla 15.1, p.214). Trace = prueba de la Traza (Mackinnon et al, 1999, t abla II, p.571); r = número de vectores de cointegración rezagos = 3.…”
Section: La Evidencia Empírica La Base De Datos Ut Ilizada Consiste Eunclassified
“…Both hypotheses have been tested experimentally in developed and developing countries and they led to mixed results. For example, in studies conducted by Chow et al (2002), Thornton (1999) and Ansari et al (1997) Wagner's law was confirmed experimentally. While in the study conducted by Ram (1986), Afxentiou and Serletis (1996) and Wahab (2004), Wagner's law could not be confirmed experimentally.…”
Section: Theoretical Principles and Literature Reviewmentioning
confidence: 88%
“…Government expenditures, including expenditure on education also affect GDP growth. As a result, a simple regression including GDP and government expenditures led to specification error (Chow et al 2002). The main objective of this study was to test the Wagner's law and the Keynesian hypothesis in the Iranian economy using data from 1991 to 2012.…”
Section: Theoretical Principles and Literature Reviewmentioning
confidence: 99%
“…6 In the Wagner's law literature, all studies conduct cointegration analysis in a bivariate system. One notable exception is Chow et al (2002), who emphasize the importance of controlling the effects of a third variable on the cointegrating relationship between government size and economic development. 7 As described later, net state fiscal transfers can be negative in Germany, and ln is undefined.…”
Section: Panel Cointegration Analysis Of Wagner's Law For Us and Gementioning
confidence: 99%